Antioxidant Feeding Does Not Impact Incidence or Severity of Liver Abscesses - H. C. Muller; C. L. Van Bibber-Krueger; J. S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2017)
Liver abscesses are a large source of economic loss in feedlot cattle. Not only do liver abscesses lead to a decrease in feedlot performance, but these livers are condemned in the abattoir and can also lead to a further decrease in carcass value due to trim loss. Tylosin phosphate is a metaphylactic macrolide drug that effectively decreases the occurrence of liver abscesses. The drug is approved by the Food and Drug Administration for over-the-counter use. However, in January 2017 the FDA will require a veterinary feed directive for medically important antibiotics (antibiotics that are used in human health) used in production animal feed. Macrolides are one class of antibiotic that will require a veterinary feed directive. A drug that is accompanied by a veterinary feed directive will require it to be used within the regulations that the FDA has set for the specific drug. This new directive is to encourage the animal production industry to use less medically important antibiotics. It is therefore important to look at alternatives to control liver abscesses in feedlot cattle. Various studies have shown that α-tocopherol acetate increases the humoral response and that ascorbate increases mononuclear lymphocyte counts. These antioxidants are also known to maintain the integrity and structure of ruminal papillae, thereby inhibiting pathogenic bacteria that lead to the formation of liver abscesses from gaining access to the portal blood and then eventually the liver. The objective of this study was to evaluate the impact of antioxidants on feedlot performance, carcass characteristics, and incidence and severity of liver abscesses in finishing heifers.
Keywords: antioxidant; liver abscesses; feedlot cattle